TYPE 2 GAUCHER DISEASE: ONSET AND EVOLUTION - CASE REPORT - Violeta Streanga; Cristina Jitareanu; Irina M. Ciomaga; Doina Mihaila; Nicolai Nistor (Amaltea Medical Publishing House, 2015)
Gaucher disease is the most common lysosomal storage disorder, with autosomal recessive transmission. The disease is due to glucocerebrosidase enzyme defi ciency, resulting in accumulation of glucocerebroside in all organs. The diagnosis is established by measuring enzyme activity. Among the clinical forms, type 2 is the rarest and has the most dismal prognosis. We present the case of an infant found at 5 months of age with neurological symptoms and his subsequent evolution with massive hepatosplenomegaly, being diagnosed with type 2 Gaucher disease.